'Imagined Balkans' meets 'imagined Africa': the contemporary practice of jembe drumming in Serbia. Issue 3 (2nd September 2022) - Nenić, Iva
ABSTRACT: This paper focuses on the jembe (djembé) as a symbol of Africanness in contemporary Serbian culture. Players' narratives often underline the universality and spirituality of distant, romanticised Africa linking these supposed features to 'archaic' aspects of Serbian and Balkan traditional music. The trope of universally adaptable rhythm has united different players, from pioneers of cross-cultural sound during late Yugoslav socialism to the proponents of present-day multiculturalism in Serbia. This paper is informed by ethnographic research with the group Đembija, a recent Belgrade-based music project, and by the use and discourse surrounding the jembe and other African instruments by other contemporary Serbian musicians. The jembe's use in world music bands serves as the basis for a diversity of ideological, poetic and musical practices. Simultaneously, the aural learning, small scale and 'slow pace' of musicianship, in contrast to the hectic everyday experience of contemporary capitalist society, acquires nostalgic resonances within Serbia's budding cross-cultural jembe playing practices.